Survey of economics : principles and tools - O'Sullivan, Arthur; Sheffrin, Steven M. (Upper Saddle River, N.J. : Pearson/Prentice Hall, 2005)
The text uses five key principles as the foundation to the study of economics and an active learning approach to help reinforce economic concepts. The principles include: the principle of opportunity cost, the marginal principle, the principle of diminishing returns, the spilover principle and the reality principle.
Includes bibliographical references and index.
osc 29/04/14
Loans
Keywords: Economics